Yield tradeoffs and weed suppression in a winter annual oilseed relay‐cropping system. (12th June 2020) - Hoerning, Cody; Wells, M. Scott; Gesch, Russ; Forcella, Frank; Wyse, Donald
Abstract: Midwest crop production is dominated by two summer annual crops grown in rotation, corn ( Zea mays L.) and soybean ( Glycine max [L.] Merr.). This rotation leaves a productivity gap during the spring and autumn. Winter oilseed crops, such as pennycress ( Thlaspi arvense L.), and winter camelina ( Camelina sativa [L.] Crantz), can fill this gap and provide ecosystem and economic benefits. The objectives of this study were to: (i) examine the tradeoffs between soybean and winter oilseed yields in the relay‐cropping system, (ii) determine legacy effects on corn 1 yr after oilseed–soybean relay‐cropping, and (iii) evaluate the weed suppression abilities of the winter oilseeds. Three sites were used across Minnesota to evaluate winter oilseeds and commodity crop yields in a relay‐cropping production system. Total seed production of the system (winter oilseed crop + soybean) was increased by 20% at one site, whereas at the other two sites, total yields were similar when compared to mono‐cropped soybean. Soybean yield was reduced at two of the three sites by 20 and 47% by the inclusion of winter oilseeds. Soybean yield was unaffected by inclusion of winter oilseeds at the third site. In the subsequent year, corn yield was unaffected by the winter oilseed treatments. Weeds were suppressed by the winter oilseeds crops. Pennycress reduced weed biomass by 97% to 100%, and camelina treatment reduced weed biomass by 85% to 87%. The inclusion of winter oilseeds in the corn–soybean cropping system can increase overall seed production and suppress early season weeds.